2023
DOI: 10.1186/s12974-023-02719-8
|View full text |Cite
|
Sign up to set email alerts
|

Inducible co-stimulatory molecule (ICOS) alleviates paclitaxel-induced neuropathic pain via an IL-10-mediated mechanism in female mice

Abstract: Chemotherapy-induced peripheral neuropathy (CIPN) is a primary dose-limiting side effect caused by antineoplastic agents, such as paclitaxel. A primary symptom of this neuropathy is pain. Currently, there are no effective treatments for CIPN, which can lead to long-term morbidity in cancer patients and survivors. Neuro-immune interactions occur in CIPN pain and have been implicated both in the development and progression of pain in CIPN and the resolution of pain in CIPN. We investigated the potential role of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…ICOS is a member of the CD28 family, a co-stimulatory receptor expressed on activated T lymphocytes 28 . First, we systematically evaluated the mRNA and protein expression patterns of ICOS in different human normal tissues and various types of tumors by bioinformatics analysis.…”
Section: Discussionmentioning
confidence: 99%
“…ICOS is a member of the CD28 family, a co-stimulatory receptor expressed on activated T lymphocytes 28 . First, we systematically evaluated the mRNA and protein expression patterns of ICOS in different human normal tissues and various types of tumors by bioinformatics analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of δOR expression on DRG sensory neurons using Oprd1 eGFP reporter mice revealed that approximately half of the reporter-positive cells in the DRG are myelinated neurons, while approximately 36% are IB4 + non-peptidergic neurons expressing the MrgprD receptor. Using established single cell RNA sequencing resources, we found that the MrgprD + subset of DRG sensory neurons not only expresses Oprd1, but also other receptors for Treg ligands, including Il10ra and Icosl, which have been implicated in suppression of pain thresholds [46][47][48] (Figure 6D). The total proportion of sensory neurons expressing the Oprd1 transcript matches previous data using Oprd1 eGFP reporter mice (Figure 6E).…”
Section: Delta Opioid Receptor Signaling On Mrgprd + Primary Afferent...mentioning
confidence: 99%
“…It is not yet understood why these signals fail to activate in neuropathic pain. “Off signals” include lipid-derived specialized pro-resolving mediators (SPMs) and anti-inflammatory cytokines such as IL-10 ( 346 348 ) and perhaps IL-6 ( 349 , 350 ). Subtypes of immune cells such as antinociceptive (M2) macrophages, pain-resolving microglia and regulatory T-cells and modulators of the gut microbiota-immune system are also involved ( 11 ).…”
Section: Failure To Resolve Chronic Neuroinflammationmentioning
confidence: 99%